Analysis of Accruals Quality on the Cost of Capital - A Case Study on Manufacturing Companies in Indonesia - Emy Rosiana Swandewi Candra; Erni Ekawati (The Indonesian Journal of Accounting Research, 2017)
Abstract: This study analyzes the effect of accruals quality on the cost of capital. Cost of capital consists of the cost of debt and cost of equity. Accrual quality is influenced by several factors which are divided into two groups: non-discretionary accruals (innate) and discretionary accruals. The sample used in this study is manufacturing companies listed in Indonesia Stock Exchange from the period of 2002 to 2013. Ordinary least square linear regressions are employed to analyze the data. The results showed that the quality of accruals negatively affects the cost of capital. However, the cost of capital of manufacturing companies in Indonesia is not affected by the innate accruals quality but only affected by the quality of discretionary accruals. The study suspects that investors may not be known to the practice of earnings management that affects accrual quality in reported earnings. Abstrak: Penelitian ini menganalisis pengaruh kualitas akrual pada biaya modal. Biaya modal terdiri dari biaya utang dan biaya ekuitas. Kualitas akrual dipengaruhi oleh beberapa faktor yang dibagi menjadi dua kelompok: non-discretionary accruals (bawaan) dan akrual diskresioner. Sampel yang digunakan dalam penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia dari periode 2002 hingga 2013. Regresi linier terkecil biasa digunakan untuk menganalisis data. Hasil penelitian menunjukkan bahwa kualitas akrual berpengaruh negatif terhadap biaya modal. Namun, biaya modal perusahaan manufaktur di Indonesia tidak dipengaruhi oleh kualitas akrual bawaan, tetapi hanya dipengaruhi oleh kualitas akrual diskresioner. Studi ini mencurigai bahwa investor mungkin tidak memiliki pengetahuan tentang praktik manajemen laba yang mempengaruhi kualitas akrual dalam laba yang dilaporkan.